2012
DOI: 10.1161/circulationaha.111.067264
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Distribution and Risk of Cardiovascular Disease

Abstract: E pidemiological, clinical, and mechanistic preclinical studies conducted in the field of cardiovascular medicine have led to remarkable progress in our understanding of nonmodifiable and modifiable risk factors for cardiovascular disease (CVD). For instance, although the prevalence of CVD had reached devastating levels in the 1950s, proper focus on the major CVD risk factors first identified at the time, such as smoking, hypertension, and high cholesterol levels, has allowed these risk factors to be targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
851
4
35

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,121 publications
(922 citation statements)
references
References 144 publications
32
851
4
35
Order By: Relevance
“…26 The use of imaging techniques such as CT and magnetic resonance imaging have improved our ability to precisely and reliably quantify individual differences in body fat distribution and to selectively distinguish subcutaneous adiposity from visceral abdominal adipose tissue. 27 The results of this study therefore suggest that excess visceral adipose tissue distribution may represent an early index of dangerous ectopic lipid deposition linked to altered myocardial lipid metabolism and eventually to impaired ventricular geometry and function. Other studies reported that the metabolic abnormalities linked to visceral obesity (i.e.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…26 The use of imaging techniques such as CT and magnetic resonance imaging have improved our ability to precisely and reliably quantify individual differences in body fat distribution and to selectively distinguish subcutaneous adiposity from visceral abdominal adipose tissue. 27 The results of this study therefore suggest that excess visceral adipose tissue distribution may represent an early index of dangerous ectopic lipid deposition linked to altered myocardial lipid metabolism and eventually to impaired ventricular geometry and function. Other studies reported that the metabolic abnormalities linked to visceral obesity (i.e.…”
Section: Discussionmentioning
confidence: 73%
“…metabolic syndrome and type-2 diabetes) are associated with increased prevalence of aortic valve calcification, 28, 29 faster progression of AS, 30 and faster degeneration of aortic bioprosthetic valves. 31 As lifestyle modification programs including regular physical activity have been shown to mobilize visceral adipose tissue and ectopic fat depots, 27 it is suggested that lifestyle modification interventions may represent interesting early options to halt or slow disease progression at both the valvular and ventricular levels in patients with AS. Considering the limited therapeutic options for AS, randomized trials may be conducted to test the added value of prevention program targeting excess visceral/ectopic adiposity for the reduction of disease progression rate and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…However, when circadian curves of estimated high-frequency components detected in obese and control subjects are compared, it becomes clear that the difference in the two curves is greater for magnitude in the daytime period between 6.00 a.m. and 2.00 p.m. This time window includes the early morning hours known to be associated with a pronounced adrenergic overdrive to the heart and peripheral vessels, and with a greater risk of sudden arrhythmic death, particularly in obese patients [2,7].…”
mentioning
confidence: 99%
“…First, unfortunately, no data are available on the relationships between the high-frequency/ low-frequency heart rate patterns and waist-to-hip ratio, which is a sensitive marker of body fat distribution [7]. This information is needed to determine whether the observed cardiac autonomic dysregulation was more pronounced in people with visceral fat obesity, or people with peripheral fat obesity, as it has been reported in obese adults [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation